Achieving fluency through perceptual-symbol practice in human-robot collaboration - Hoffman, Guy; Breazeal, Cynthia (2008 3rd ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2008)
We have developed a cognitive architecture for robotic teammates based on the neuro-psychological principles of perceptual symbols and simulation, with the aim of attaining increased fluency in human-robot teams. An instantiation of this architecture was implemented on a robotic desk lamp, performing in a human-robot collaborative task. This paper describes initial results from a human-subject study measuring team efficiency and team fluency, in which the robot works on a joint task with untrained subjects. We find significant differences in a number of efficiency and fluency metrics, when comparing our architecture to a purely reactive robot with similar capabilities.